TINJAUAN PELAKSANAAN PEMBELAJARAN REMEDIAL PADA MATA PELAJARAN FISIKA KELAS VIII SMP XAVERIUS LUBUKLINGGAU - Meyumi Uskarina (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2019)
This study aims to describe the implementation of remedial learning by physics teachers at Xaverius Lubuklinggau Middle School and to determine the obstacles experienced by teachers in implementing remedial learning. The problem of this research is how is the implementation of remedial learning in physics in Xaverius Lubuklinggau Middle School ?. What are the constraints experienced by remedial implementation? This research uses descriptive qualitative methods, namely methods that describe research data, classify and interpret research data. Data collection was done by questionnaire interviews and documentation. From the results of the study note that student activity at the time of remedial included less viewed from the lack of seriousness of students in implementing remedial. Difficulties of students in learning physics vary. The thing that causes students difficulties in learning physics is students who have not mastered the material taught by the teacher, the teacher is not maximally giving material to students. But the factors that cause students learning difficulties are caused from within the students themselves. The results of this study also showed that the remedial implementation method carried out by physics teachers at Xaverius Middle School was in the form of assignments. The obstacle experienced by the teacher in remedial implementation is the lack of seriousness of students following the remedial that there are still students who are not present during remedial implementation.